Planetary nebulae in the magellanic clouds - P. Leisy (Revista Mexicana de Astronomía y Astrofísica, 2000)
We present optical and UV observations of PNe and derive their abundancesand the implications for chemical evolution. We observe the HBB reaction andalso an oxygen depletion via the ON reaction in the more massive stars, and anoxygen production (like carbon) during the 3rd dredge-up (the e ect is ecient atlower metallicity). Oxygen cannot be used to derive the initial composition of theprogenitor star, we have to use other elements like sulfur or argon.